Protection of text using SHA1 and Base64 - Taha, Imad; Alahmad, Mohammad; Ahmad, Hanadi (2012)
Protection of information is a prerequisite demand in the world of computers today. Protection of information can be accomplished in different methods. The main objective of the use of the protection of information is to protect data and information in order to achieve privacy. This paper discusses two methods of protection of information, an encryption method called Base64, which is a set of encoding schemes that convert the same binary data to the form of a series of ASCII code. Also, The SHA1 hash function is used to hash the encrypted file performed by Base64. As an example of an ASCII code, Arabic letters are used to represent the texts. So using the two protection methods together will increase the security level for protecting the data.